Commodified bodies : organ transplantation and the organ trade - Decker, Oliver, 1968-; Rendall, Steven (New York : Routledge, Taylor & Francis Group, 2016)
"Commodified Bodies examines the social practice of organ transplantation and trafficking and scrutinises the increasingly neoliberal tendencies in the medical system. It analyses phenomena such as the denomination of human body parts as "raw materials" and "commodities," or the arguments used by the proponents for a free market solution. Moreover, it argues that modern medicine is still linked with its religious roots. The commodification of body parts is seen not as an imperialistic act of the market, but as the end of a historical process as the notion of "fetishism" links the market with the body. Marx's concept of commodity fetishism and Sigmund Freud's theory of the perverted use of objects are modified and adapted to the reconstruction of the joint beginnings of market and medicine"--
"Commodified Bodies examines the social practice of organ transplantation and trafficking and scrutinises the increasingly neoliberal tendencies in the medical system. It analyses phenomena such as the denomination of human body parts as "raw materials" and "commodities," or the arguments used by the proponents for a free market solution. Moreover, it argues that modern medicine is still linked with its religious roots. The commodification of body parts is seen not as an imperialistic act of the market, but as the end of a historical process as the notion of "fetishism" links the market with the body. Marx's concept of commodity fetishism and Sigmund Freud's theory of the perverted use of objects are modified and adapted to the reconstruction of the joint beginnings of market and medicine"--
Includes bibliographical references (pages 183-202) and index.
Keywords: Transplantation of organs, tissues, etc; Donation of organs, tissues, etc. -- Economic aspects; Organ trafficking; Commodity fetishism; SOCIAL SCIENCE / Sociology / General; SOCIAL SCIENCE / Disease & Health Issues; MEDICAL / General; Print books